Anticipated effort and morality of segregated versus aggregated volunteering. (28th January 2021) - Henderson, Marlone D.; Jung, Haesung; M. Baker, Erin; Wakslak, Cheryl J.
Abstract: Does the way individuals think about the burdens and benefits of giving time to charity depend on how that time is distributed? Prior work shows that the assessment of a whole is different than the assessment of the sum of its parts. Drawing on this work, we demonstrate that when a volunteer experience is segregated into multiple parts (vs. aggregated into a whole)—for example, volunteering 4 h a day for 2 days versus 8 h in a single day—individuals expect the process to feel less effortful but also the outcome to feel less morally right. In addition, we find that contribution size has a moderating effect on anticipated effort (but not on anticipated morality). Lastly, we find that individuals who focus on minimizing the effort involved in volunteering (vs. maximizing the impact of volunteering) show a greater likelihood of volunteering in a segregated (vs. aggregated) manner. We discuss theoretical and practical implications of these findings.